PENINGKATAN HASIL BELAJAR LARI SPRINT MELALUI PENDEKATAN SAINTIFIK DAN PENDEKATAN BERMAIN PADA SISWA KELAS VII SMP NEGERI 15 - Abdul Harris Handoko; Trisna Br Sembiring (JURNAL TEMATIK, 2019)
This study aims to know increasing of learning outcome of sprint runningthrough the scientific approach and the playing approach to the seventh grade students of15 medan public junior high school. This research method is Classroom Action Research.Judging from the preliminary data on the results of learning to run a sprint, only 12students completed (32.5%) and 25 students who did not complete (67.5%). After the firstcycle of action, students who completed 20 people (54.05%) and students who have notfinished 17 people (45.94%) classically. Then in the second cycle students completed 32people (86.48%) and students who had not finished 5 people (13.51%). The average valueof student learning outcomes in the initial data is (44.56%) (complete), in the cycle test 1the average value of student learning outcomes increases to (62.58) (complete), on theimplementation of the cycle II test the completeness of student learning has reached(79.21%). The percentage of students 'mastery learning in the initial data was 32.5%, inthe cycle I test it increased to 67.5% and in the second cycle the percentage of students'mastery learning had reached 79.21%. The increase in the average value of learningoutcomes from the initial test to the first cycle test is 15 and the increase in the averagevalue of learning outcomes from test I to cycle II is 40.54 and the increase in the averagevalue from the initial test to cycle I is 32, 5. And the increase from the first cycle test tothe second cycle test was 86.48%.